The history of foreign exchange - Einzig, Paul. (London : Macmillan; New York : St Martin's Press, 1962)
To cover systematically the history of foreign exchange and is divided into chronologically based sections: Part I deals with the Ancient Period (primarily Greece and Rome, though also earlier civilizations), Part II the Medieval Period, Part III the Early Modern Period (sixteenth to eighteenth centuries), Part IV the Nineteenth Century (to World War I), Part V 1914-1960, and Part VI (added in the second edition) the 1960s. Other issues covered include: foreign exchange system as in practice; trends and exchange rate; and theory and policy respectively.
Includes bibliographical references and index.
haz 12/04/2019
Loans
Keywords: Foreign exchange; Foreign exchange - history; Foreign exchange - ancient period; Foreign exchange theory and policy